2020
DOI: 10.3389/fnins.2020.00647
|View full text |Cite
|
Sign up to set email alerts
|

Levodopa Changes Functional Connectivity Patterns in Subregions of the Primary Motor Cortex in Patients With Parkinson’s Disease

Abstract: Background The primary motor cortex (M1) is a critical node in Parkinson’s disease (PD)-related motor circuitry; however, the functional roles of its subregions are poorly understood. In this study, we investigated changes in the functional connectivity patterns of M1 subregions and their relationships to improved clinical symptoms following levodopa administration. Methods Thirty-six PD patients and 37 healthy controls (HCs) were enrolled. A formal levodopa challenge t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 95 publications
(106 reference statements)
6
14
0
Order By: Relevance
“…In addition to the improvement of motor performance, the normalization of impaired brain functional network organization might be another indicator of a patient's responsiveness to levodopa [13]. Studies have shown that cortical functional connectivity is increased after levodopa administration, especially in the motor cortex [13][14][15][16]. It is known that the dysfunction of somatomotor cortex is an important underlying factor for the motor symptoms of PD [16], and that the somatomotor cortex is innervated by both dopaminergic and noradrenergic projections [17].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the improvement of motor performance, the normalization of impaired brain functional network organization might be another indicator of a patient's responsiveness to levodopa [13]. Studies have shown that cortical functional connectivity is increased after levodopa administration, especially in the motor cortex [13][14][15][16]. It is known that the dysfunction of somatomotor cortex is an important underlying factor for the motor symptoms of PD [16], and that the somatomotor cortex is innervated by both dopaminergic and noradrenergic projections [17].…”
Section: Introductionmentioning
confidence: 99%
“…PD was proposed as a disconnection syndrome (Göttlich et al, 2013). Decreased connection within the SMN was identified in patients with PD compared to HCs (Wang et al, 2021), and the results were validated in drug-naïve patients with PD in resting-state analysis (De Micco et al, 2021), supporting that the dysfunction of cortexbasal ganglia circuits participate in the PD pathophysiology (Lindenbach and Bishop, 2013;Burciu and Vaillancourt, 2018;Shen et al, 2020). Focused on the dynamics, our results provide further evidence of the significance of SMN abnormality in the mechanism of PD, in accord with a recent dFC study (De Micco et al, 2021).…”
Section: Discussionmentioning
confidence: 81%
“…Meanwhile, the significantly decreased lrFCD was mainly found in the medial frontal gyrus. Statistical maps were corrected with the Gaussian random field method at the threshold of voxel P < 0.001, cluster P < 0.05 ( 31 ).…”
Section: Resultsmentioning
confidence: 99%